2002
DOI: 10.1038/nn866
|View full text |Cite
|
Sign up to set email alerts
|

Parallel processing in high-level categorization of natural images

Abstract: Models of visual processing often include an initial parallel stage that is restricted to relatively low-level features, whereas activation of higher-level object descriptions is generally assumed to require attention. Here we report that even high-level object representations can be accessed in parallel: in a rapid animal versus non-animal categorization task, both behavioral and electrophysiological data show that human subjects were as fast at responding to two simultaneously presented natural images as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
201
3
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(231 citation statements)
references
References 14 publications
24
201
3
1
Order By: Relevance
“…So detection rates of 80% (when no people were present) could be taken to suggest full attention-free processing, consistent with claims by Rousselet et al (2002) and by Li et al (2002). To counter this argument, we wish to make the point that high detection rates need not imply full identification and binding.…”
Section: Single-target Experiments (1-3)mentioning
confidence: 71%
“…So detection rates of 80% (when no people were present) could be taken to suggest full attention-free processing, consistent with claims by Rousselet et al (2002) and by Li et al (2002). To counter this argument, we wish to make the point that high detection rates need not imply full identification and binding.…”
Section: Single-target Experiments (1-3)mentioning
confidence: 71%
“…Previous studies have shown that object recognition is a rapid process. For example, it takes humans and monkeys a few hundred milliseconds to detect an animal in a natural scene [4,26,30]. In our current study, the representational paintings were cluttered scenes that included landscapes, still life, and religious images.…”
Section: Discussionmentioning
confidence: 97%
“…Behavioral and electrophysiological studies in humans and monkeys have suggested that object recognition is a rapid process that can be achieved within a few hundred milliseconds [4,26,30]. Moreover, it has been shown that identification of objects within natural scenes is facilitated when the context is meaningful [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, recent studies in visual categorization lend some support to the existence of early (i.e., preattentive) feature binding processes (e.g., Li, VanRullen, Koch, & Perona, 2002;Rousselet, Fabre-Thorpe, & Thorpe, 2002). In these studies, observers determined whether a natural scene contained an instance of a target category (e.g., animal).…”
Section: Discussionmentioning
confidence: 99%